The Multilayered Interlaced Network (MIN) in the sporoplasm of the Microsporidium Anncaliia algerae is derived from Golgi. (14th January 2013) - Takvorian, Peter M.; Buttle, Karolyn F.; Mankus, David; Mannella, Carmen A.; Weiss, Louis M.; Cali, Ann
Abstract This study provides evidence for the Golgi‐like activity of the multilayered interlaced network (MIN) and new ultrastructural observations of the MIN in the sporoplasm of Anncaliia algerae, a microsporidium that infects both insects and humans. The MIN is attached to the end of the polar tubule upon extrusion from the germinating spore. It surrounds the sporoplasm, immediately below its plasma membrane, and most likely maintains the integrity of the sporoplasm, as it is pulled through the everting polar tube. Furthermore, the MIN appears to deposit its dense contents on the surface of the sporoplasm within minutes of spore discharge thickening the plasma membrane. This thickening is characteristic of the developmental stages of the genus Anncaliia. The current study utilizes transmission electron microscopy (TEM), enzyme histochemistry, and high voltage TEM (HVEM) with 3D tomographic reconstruction to both visualize the structure of the MIN and demonstrate that the MIN is a Golgi‐related structure. The presence of developmentally regulated Golgi in the Microsporidia has been previously documented. The current study extends our understanding of the microsporidial Golgi and is consistent with the MIN being involved in the extracellular secretion in Anncaliia algerae. This report further illustrates the unique morphology of the MIN as illustrated by HVEM using 3D tomography.